Application of imaging modalities for endovascular thrombectomy of large core infarcts in clinical practice - Hai Zeng; Qingfeng Zhu (Frontiers in Neurology, 2024)
Four randomized controlled trials of large infarct core volume (LICV) included three imaging modalities: non-contrast CT (NCCT)-Alberta Stroke Program Early CT Score (ASPECTS), diffusion-weighted imaging (DWI)-ASPECTS, and NCCT-ASPECTS combined with CTP (CT perfusion). However, there is no clear consensus on the optimal imaging modality for endovascular thrombectomy (EVT) trials of large core infarcts. The variety and complexity of imaging modalities make it difficult to apply them in clinical practice. By familiarizing ourselves with these imaging modalities, we can better apply them in the clinic and correctly screen patients with large core infarcts in the anterior circulation who can benefit from EVT therapy.